2010
DOI: 10.1007/s00259-010-1531-0
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide imaging of bone marrow disorders

Abstract: Noninvasive imaging techniques have been used in the past for visualization the functional activity of the bone marrow compartment. Imaging with radiolabelled compounds may allow different bone marrow disorders to be distinguished. These imaging techniques, almost all of which use radionuclide-labelled tracers, such as 99mTc-nanocolloid, 99mTc-sulphur colloid, 111In-chloride, and radiolabelled white blood cells, have been used in nuclear medicine for several decades. With these techniques three separate compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 65 publications
(76 reference statements)
0
51
0
1
Order By: Relevance
“…The recognition of the two different marrow types is founded on the concept-documented both by pathology [22] and by imaging studies [2,9,10]-that vertebral bodies are mainly occupied by red BM. Actually, our approach showed that FDG uptake in this bone region is higher than in the rest of the IBV and displays a gaussian distribution.…”
Section: Recognition and Measurement Of Whole-body Intraosseous Spacementioning
confidence: 99%
See 2 more Smart Citations
“…The recognition of the two different marrow types is founded on the concept-documented both by pathology [22] and by imaging studies [2,9,10]-that vertebral bodies are mainly occupied by red BM. Actually, our approach showed that FDG uptake in this bone region is higher than in the rest of the IBV and displays a gaussian distribution.…”
Section: Recognition and Measurement Of Whole-body Intraosseous Spacementioning
confidence: 99%
“…In the present study, we propose a new approach to this issue exploiting the advantages of hybrid PET/CT technology. FDG imaging has been already used to document BM infiltration by cancer [2,[10][11][12][13] and to monitor the haematopoietic response to chemo-and radiotherapy in specific bone regions [14]. The aim of our methods was to extend this clinically validated tool to provide a first description of the extension and distribution of the BM throughout the whole skeleton of living humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scintigraphic techniques including 111 In-chloride and 99m Tc-labelled colloids can be used to visualize different physiological aspects of the bone marrow activity [22][23][24], but do not target the myeloproliferation or the state of chronic inflammation within the bone marrow compartment. 18 F-FDG PET/ CT is an established imaging modality for detection of various haematological neoplasms [23,25], and has become a useful tool for response assessment in haematooncology [26].…”
mentioning
confidence: 99%
“…In a multicenter study of symptomatic multifocal osteonecrosis, various authors suggested that a total body BSc may be the most cost-effective means of screening for multifocal involvement [26], when the multifocal lesions are not recognizable on plain radiography before localized by BSc technology [27]. The SCD osteonecrosis could be completely clinically silent [28].…”
Section: Bone Scintigraphymentioning
confidence: 99%